The Influence of the Korean Wave and the Hedonism Lifestyle on the Decision to Purchase Official/Unoffical Aespa Merchandise in Indonesian - Cindy Fransisca; Afrianti Elsye Vanomy (Jurnal Bisnis dan Manajemen, 2024)
This investigation seeks to elucidate the impact of the Korean Wave phenomenon and hedonistic consumer behavior on purchasing decisions regarding official and unofficial AESPA merchandise in Indonesia. The findings are anticipated to inform SM Entertainment's marketing strategy development, with particular emphasis on leveraging the Korean Wave and hedonistic lifestyle factors. Employing a quantitative research methodology, this study utilizes multiple linear regression analysis, executed via IBM SPSS version 29. The sampling procedure adheres to a non-probability approach, specifically utilizing judgment sampling. The study population comprises 100 Indonesian MY (AESPA fan community members) who engage with AESPA's music at a minimum frequency of once per month. The results demonstrate that both the Korean Wave and hedonistic lifestyle variables exert statistically significant influences on purchasing decisions, both independently and in conjunction.Keywords Korean Wave, Hedonism Lifestyle, Purchase Decision